Edukasi Pengendalian Vektor Aedes aegypti dan Pelatihan Pembuatan Kompos Sederhana di SD Genta Saraswati, Gianyar - Sintya, Erly; Agung Aryastuti, Anak Agung Sri; Maha Putra, I Nyoman Gede (Poltekkes Kemenkes Denpasar, 2026)
Background: Dengue fever remains a major public health concern in Gianyar Regency, Bali, with rising incidence strongly associated with Aedes aegypti as the primary vector. School environments are critical settings for early prevention due to children’s vulnerability and the presence of potential mosquito breeding sites. Integrating vector control education with environmental management is therefore essential to reduce dengue risk and promote sustainable behaviors.Objective: This program aimed to enhance knowledge and practical skills of students and teachers at Genta Saraswati Elementary School, Gianyar, regarding Aedes aegypti vector control and organic waste management through composting and vermicomposting.Method: The Community Partnership Program (PKM) was implemented through interactive education on Aedes aegypti biology, dengue prevention, identification of breeding sites, and hands-on composting and vermicomposting training using a Montessori-based experiential learning approach. Program effectiveness was assessed using pre- and post-tests.Result: Participants’ knowledge increased significantly, with post-test scores exceeding 70%. Simple composting and vermicomposting facilities were successfully established and utilized as learning media.Conclusion: Integrated vector control education and composting training effectively improved health awareness and environmental responsibility in a school-based setting. Keywords: Dengue prevention; vector control; composting;